Impact of obstetric care during delivery and the confinement for the satisfaction and the safety feeling of patients - Stadnicka, Grażyna; Górska, Beata; Iwanowicz-Palus, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. The satisfaction and a sense of security patients on maternity ward is determined inter alia, by the actions taken by the midwife. The aim of this study was to evaluate the satisfaction of patients of on maternity ward provided by midwives. Material and methods. The study was conducted by using a diagnostic survey on author’s questionnaire survey among 150 patients staying in maternity wards: SPSK No. 4 and SPSW in Lublin and Biłgoraj Hospital in the period from November 2009 to January 2010. Used the test in the statistical analysis chi2 test. Results. Two-fifth (40.0%) of respondents lived in the countryside, remaining (60.0%) respondents were residents of towns. Results of this study show that nearly three-quarters of the women (73.3%) had a choice of hospital where the labour took place. This possibility as far as statistical significant (p < 0.05) had influence on the respondents feel safe staying in the maternity ward. It is also important to have support shown by the midwife to the patient’s during delivery. The respondents assessed the scale of 1-5 factors influencing satisfaction with maternity care at the labour ward. Obtaining help from a midwife in a difficult situation (pain felt during the contraction, fear of the unknown), three quarters (72.7%) of women were evaluated highest. More than half of the respondents considered as very important friendliness of staff (64.0%) and objective treatment of woman in labour (56.0%). Conclusions. The chance of the choice place of the labour seems to be important for the patient felt a sense of security during the hospitalization. It is important for women during labour has the support shown by the midwife, during the stay on the labour ward.